Digital Marketing and Corporate Social Responsibility on Brand Building: A Study of Daraz - Dhakal, Shreena; Dhungana, Kishore (Apex Journal of Business and Management, 2024)
This research aims to investigate the relationship between digital marketing, corporate social responsibility (CSR), and their combined impact on brand building, with a specific focus on Daraz. The research is characterized as quantitative in nature. SPSS software facilitated data analysis, encompassing respondent profiling, descriptive analysis, and correlation and regression calculations. Correlation analysis revealed a significantly positive relationship among all independent variables (social media marketing, promotional activities, social disclosure, environmental disclosure) and the dependent variable (brand building). Hypotheses were formulated to assess the significance of these relationships. Results indicated that promotional activities and environmental disclosure significantly impact brand building. However, multi-collinearity issues hindered the testing of hypotheses related to social media marketing and social disclosure. Despite contributing valuable insights, this research has limitations. The focus on only four variables may overlook other factors influencing brand building. Additionally, the sample size is confined to respondents with internet access, limiting the generalizability of the results to the broader population. These considerations underscore the need for caution when interpreting and applying the findings beyond the scope of this study.